The Optical Properties of Aluminum Doped CdO Thin Films Prepared by Vacuum Thermal Evaporation Technique - Maki, Samir A.; Shehab, Alia A.A.; Salih, Ayad A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, thin films of undoped and Al-doped CdO with (0.5, 1 and 2) wt.%  were prepared by using thermal vacuum evaporation on glass substrate at room  temperature. The optical absorption coefficient (Î±) of the films was determined from transmittance spectra in the range of wavelength (400-1100) nm. The spectral transmission and the optical energy band gap decrease from 75% and 2.24 eV to 20%  and 2.1 eV respectively depending upon the Al content in the films, also our studies include the calculation of  the optical constants (refractive index, extinction coefficient, real and imaginary part of dielectric constant) as a function of photon energy.  It is evaluated that the optical band gap of the CdO film could be controlled by Al-doping.  The width of localized states in the optical band gap of the films increases with the increase of Al content. The improvement of the optical constant of Aldoped CdO has potential applications as transparent conducting oxide for different optoelectronic device applications.